Essentials of musharakah and mudarabah: Islamic texts on theory of partnership - Sadique, Muhammad Abdurrahman (IIUM Press, International Islamic University Malaysia, 2009)
Essentials of Musharakah and Mudarabah provides a comparative summary of the discussion on joint ventures and partnership as found in the major texts of the schools of Islamic law. The first part presents an outline of the salient features of partnership and financing. It discusses issues pertaining to shirkah al-milk (joint ownership), shirkah al-'aqd (contractual ownership) and its various types, mudarabah (fund management), the relevant conditions and important roles, together with their rationales as expounded by Muslim jurists. The second part comprises an in-depth survey of the theory pertaining to the essence of shirkah in the major schools of Islamic law and how this theory is related to some important aspects of partnership such as the nature of capital. The text is concise, avoiding detailed expositions and illustrations. Necessary explainations and reference to original works in Arabic are provided in the footnotes. The work should prove to be of interest to academics and students of Islamic law and finance, who desire to understand the fiqhi discussion on the topic, and read the text in English.